Leaky-wave radiation behavior from a double periodic composite right/left-handed substrate integrated waveguide - Cheng, Jin (2013)
A double periodic composite right/left-handed ( DP-CRLH ) substrate integrated waveguide (SIW) is proposed based on the transmission line theory. A new leaky-wave radiation is observed at low frequency below the left-handed passband in addition to the composite right/left-handed property. First, the equivalent circuit of the proposed structure is analyzed, and dispersion characteristics are obtained including the expression for the cutoff frequencies. It is noted that transmission lines double periodically loaded with either alternate capacitances, or alternate inductances will contribute the new leaky-wave behavior. Next, SIW implementation of a DP-CRLH transmission line is designed and illustrated with simulated and experimentally demonstrated results. The electric field distribution plots are extracted from a full-wave simulation tool and exhibit the forward and backward wave propagation in the new leaky-wave region and the typical left-handed region, respectively. Finally, a compact leaky-wave antenna based on the DP-CRLH SIW is designed, and the radiation characteristics are tested and demonstrated to exhibit forward radiation at the new leaky-wave region from 5.2 to 5.8 GHz (covering IEEE 802.11a band) and frequency scanning from backward to forward directions in the left-handed and conventional right-handed region from 12.6 to 17.8 GHz.